MiR-143-3p Increases the Radiosensitivity of Breast Cancer Cells Through FGF1 - Wang, Dewen; Wang, Chunying; Sun, Lei; Lu, Xiang; Shi, Jiangwei; Chen, Jing; Zhang, Xuesong (Cellular and Molecular Biology, 2022)
Breast cancer is a common malignant tumor in women. At present, the main treatment for breast cancer is radiotherapy. Due to the difference in radiosensitivity between individuals or tumor cells, the effect of radiotherapy is not good. Therefore, in radiotherapy, how to use various auxiliary means to reduce the radiation resistance of tumor, Therefore, it has become an important research topic to improve the radiosensitivity of the tumor. Fibroblast growth factor-1 (FGF1) plays an important role in tumor migration. Therefore, the study of miR-143-3p increasing the radiosensitivity of breast cancer cells through FGF1 is proposed in this paper. In this study, a control group experiment was set up to study. During the experiment, the relative expression of miR-143-3p was detected by fluorescent quantitative PCR of miRNA, and the cell irradiation experiment was created to analyze the radiosensitivity of breast cancer cells by comparing their survival fraction. The results of this study showed that when the radiation dose was 0, the survival scores of the three groups were all 1. The survival fraction of the experimental group decreased from 0.26 ± 0.045 to 0.068 ± 0.008 when the dose was added to 4Gy. The survival fraction of the experimental group was always greater than that of the two control groups. The results of this study show that miR-143-3p can increase the radiosensitivity of breast cancer cells through FGF1.